Yell Video Technique to Develop the Third Semester Students' Ability in Present tense - Safra Apriani Zahraa (ELT Worldwide: Journal of English Language Teaching, 2020)
Abstract: The purpose of this study was to determine the level of third semester students’ ability in mastering simple present tense using a Yell Video technique. The research method used was a Classroom Action Research (CAR). The research data included the results of the pre test and post test regarding the simple present tense. The data collection techniques used were classroom observation, interviews, notes, pre test and post test. The results of this study indicated that the use of a Yell Video can improve students' ability to understand the simple present tense.